PENGARUH MUTU PELAYANAN KEBIDANAN TERHADAP KEPUASAN PASIEN POLI KIA RUMAH SAKIT UMUM DAERAH PRAYA KABUPATEN LOMBOK TENGAH - Eva Silfia; Hadi Suryatno; Nurhidayah (LPPM STIKES Mataram, 2024)
Background: The services currently employed to evaluate the performance of health service organizations are often limited in scope and temporary. It is the responsibility of the government to provide comprehensive health services that promote maternal and infant well-being. The quality of these health services serves as a crucial indicator of healthcare effectiveness, contributing significantly to patient satisfaction. Purpose: This study aims to analyze the influence of midwifery service quality on patient satisfaction in Maternal and Child Health Polyclinic, Praya General Hospital, Central Lombok Regency. Method: This research utilized a quantitative correlational design with a cross-sectional approach, involving a population of 95 individuals. Data were collected in March 2024 using a questionnaire administered to pregnant patients at the Maternal and Child Health Polyclinic, Praya General Hospital, Central Lombok Regency. The sampling was conducted through an accidental sampling technique. Result: Statistical analysis using the Chi-Square test with a sample of 95 respondents revealed a p-value of 0.022, which is less than the significance level of α = 0.05. Furthermore, the Relative Risk (RP) value was 2.784, indicating that individuals experiencing poor service quality were 2.784 times more likely to report dissatisfaction compared to those receiving good service quality. In conclusion, the results demonstrate an influence between the quality of midwifery services and patient satisfaction in Maternal and Child Health Polyclinic, Praya General Hospital, as indicated by a p-value of 0.022, which is less than the significance level of α = 0.05. Suggestions:The officers at the KIA Polyclinic at Praya Regional Hospital can provide better service. And it is hoped that RSUD will complete the facilities and infrastructure to support services.